Research Progress of N6-Methyladenosine in the Cardiovascular System - Zheng, Nan (Med Sci Monit, 2020)
According to the World Health Organization cardiovascular disease risk charts, the mortality rate of cardiovascular diseases in people is still high. The medical expenses caused by cardiovascular diseases are increasing daily, and the medical burden is becoming heavier; as such, it is imperative to prevent and cure cardiovascular diseases. A large number of scholars are analyzing the pathogenesis of cardiovascular diseases from various perspectives. Recent findings suggest that N6-methyladenosine (m6A) plays a multifaceted role in the cardiovascular system. m6A is a methylated modification product on RNA molecules and exists on various RNA molecules. It is one of the most common epigenetic modifications discovered to date. It regulates the expression of genes and subsequent responses. The amount of m6A is determined by methylases (writers) and demethylases (erasers). The third type of proteins, readers, selectively bind to m6A to regulate RNA stability and gene expression. In this paper, the relationship between m6A and related enzymes and cardiovascular structure and function was reviewed based on recent research results regarding the cardiovascular system.